Geopolymer composition and hardened geopolymer
Patent Information
- Application Number
- JP2024015343
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-02-05
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2041-09-29
AI Technical Summary
【0021】 本発明によれば、産業副産物を効率的に有効利用しつつ、重金属の溶出を抑制することができる硬化体を製造可能であり、かつ、長時間における高流動性の確保と短期間での簡便な手法による高強度発現とを両立することができるジオポリマー組成物を提供することができる。
Smart Images

Figure 0007638406000001 
Figure 0007638406000002 
Figure 0007638406000003
Abstract
Description
Technical Field
[0001] The present invention relates to a geopololymer composition and a cured product thereof, a geopololymer cured body.
Background Art
[0002] Hardened bodies such as concrete, mortar, artificial stone, and building hardened members generally contain cement. However, when manufacturing these hardened bodies using cement, there is a problem that a large amount of CO2 is emitted during firing. Therefore, a method for manufacturing these hardened bodies that is environmentally suitable without using cement has attracted attention, and in particular, a manufacturing method using the geopololymer method has been actively studied.
[0003] The geopololymer method is a technique for manufacturing artificial rock by joining powders using a polycondensate of silicon or aluminum as a binder. The geopololymer cured body formed by this geopololymer method is manufactured by causing a pozzolanic reaction using an active filler that is an aluminosilicate source and an alkaline aqueous solution (also referred to as an "alkali stimulant") as an activator. As the active filler, natural products such as kaolin and clay, fly ash, silica fume, blast furnace slag, rice husk ash, etc. can be used. As the alkaline aqueous solution, aqueous solutions such as sodium hydroxide and water glass can be used.
[0004] For example, Patent Document 1 describes a geopololymer composition comprising an active filler containing at least one of fly ash, blast furnace slag, sewage incineration sludge, and kaolin, silica or a silica compound, and an alkaline aqueous solution, wherein the molar ratio of the amount of silica to the amount of alkali contained in the solution is less than 0.50, the molar ratio of the amount of alkali to the amount of water contained in the solution is 0.075 or more, and the active filler has a calcium compound content x of 0 < x ≤ 30 (vol%), and a geopololymer composition with improved durability is described.
Prior Art Documents
Patent Documents
[0005] [Patent Document 1] Patent No. 6284388 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the hardened geopolymer compositions that have been studied and reported to date have many problems that prevent them from being put to practical use as substitutes for hardened materials such as concrete and mortar that use cement.
[0007] Specifically, many of the geopolymer compositions reported to date have a too fast hardening rate, and after about an hour from mixing, their fluidity drops significantly and they begin to set. If the hardening rate of a geopolymer composition is too fast, it becomes difficult to handle hardened products such as concrete and mortar at the manufacturing site. On the other hand, in order to slow down the hardening rate and maintain good fluidity for as long as possible, a large amount of water may be added to the geopolymer composition. However, when a large amount of water is added, a long period of curing is required for the hardened geopolymer body to gain strength, and the strength of the hardened body produced cannot be said to be sufficient. Alternatively, the period required to gain strength can be shortened by replacing normal curing such as underwater, wet, or in air with steam curing, but steam curing is expensive, so the manufacturing cost increases significantly.
[0008] Thus, according to the manufacturing methods for hardened bodies using geopolymer compositions reported to date, it is difficult to obtain a hardened body with the desired high strength in a short period of time while maintaining good fluidity for a long period of time using a simple method.
[0009] In addition, the geopolymer composition can use many industrial by-products (such as coal ash) (hereinafter, simply referred to as "by-products") as the raw material active filler. Therefore, it is advantageous from the viewpoint of reducing the environmental load. However, by-products such as untreated coal ash have different compositions, particle sizes, heavy metal contents, etc. in individual powders, etc., and have variations in quality. Therefore, when untreated by-products are used as they are in the production of geopolymer compositions, it is expected that the variations in quality will affect the physical properties of the geopolymer composition and its hardened body. On the other hand, JIS A 6201:2015 specifies the method of evaluating whether the quality of fly ash for concrete meets the standards, and the standards for the same. Therefore, in general, when using coal ash as a by-product, it is preferable to treat the coal ash to conform to the standards.
[0010] In addition, when a geopolymer composition is produced as a hardened product using by-products such as coal ash, it is an important issue whether heavy metals that affect the environment or human body will be eluted. However, there have been no reports to date that such issues have been considered in the case of hardened products such as concrete made from geopolymer compositions. Therefore, the conditions for suppressing the elution of heavy metals from hardened geopolymer products containing by-products such as coal ash have not been clarified. Specifically, for example, hardened geopolymer compositions are applied to precast products such as pavement and boundary blocks in hot spring areas and railway sleepers due to their high heat resistance and acid resistance. However, in such application cases, details regarding the elution of heavy metals from precast products that come into contact with soil, rivers, etc. have not been clarified.
[0011] In this way, when coal ash by-product is used as it is without pretreatment in the production of hardened geopolymer bodies, it is necessary to address not only the impact of quality variations, but also the problem of heavy metal elution. However, Patent Document 1 does not mention or suggest such problems as the variation in quality of by-products such as coal ash or the elution of heavy metals from the hardened body.
[0012] Therefore, there is a demand for a new geopolymer composition that can address not only the problems of high fluidity and high strength in a short period of time in geopolymer compositions, but also the problem of quality variation when by-products are used as raw materials, and the new issue of suppressing heavy metal leaching when the composition is hardened.
[0013] Therefore, the present invention aims to provide a geopolymer composition that can produce a hardened body that can suppress the elution of heavy metals while efficiently utilizing industrial by-products, and can simultaneously ensure high fluidity over a long period of time and exhibit high strength in a short period of time using a simple method. [Means for solving the problem]
[0014] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention includes the following preferred embodiments.
[0015] A geopolymer composition according to a first aspect of the present invention comprises an active filler, an aggregate, water, an activator, and a dispersant, The dispersant is a polycondensate-based dispersant containing polyalkylene glycol monophenyl ether as a partial structure, and the amount of the dispersant is 0.1% by mass to 2.0% by mass with respect to the total mass of the geopolymer composition. The active filler contains coal ash and ground granulated blast furnace slag that have not been treated to conform to the standard for fly ash for concrete specified in JIS A 6201, in a total amount of 85% by mass or more.
[0016] In the above geopolymer composition, the active filler preferably further comprises silica fume.
[0017] In the above geopolymer composition, the aggregate preferably comprises at least one of blast furnace slag fine aggregate, blast furnace slag coarse aggregate, and natural aggregate.
[0018] In the above-mentioned geopolymer composition, it is further preferable that the uniaxial compressive strength of the hardened product of the geopolymer composition measured in accordance with JIS A 1108 is 10 MPa or more at an age of 7 days.
[0019] In the above-mentioned geopolymer composition, it is particularly preferable that the bending crack resistance strength of the hardened material of the geopolymer composition measured in accordance with JIS A 5371 is 3.5 kN·m or more at an age of 5 days.
[0020] The geopolymer hardened body according to the second aspect of the present invention is a hardened product of the geopolymer composition according to the first aspect described above. Effect of the Invention
[0021] According to the present invention, it is possible to produce a hardened body that can effectively utilize industrial by-products while suppressing the elution of heavy metals, and it is possible to provide a geopolymer composition that can simultaneously ensure high fluidity over a long period of time and achieve high strength in a short period of time using a simple method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The inventors of the present invention have conducted various studies on a geopolymer composition that can produce a hardened body capable of suppressing the elution of heavy metals and at the same time can achieve both high fluidity over a long period of time and high strength in a short period of time. Then, they focused on the types and amounts of dispersants and active fillers to be contained in the geopolymer composition and completed the present invention.
[0023] Specifically, the geopolymer composition according to this embodiment contains an active filler, aggregate, water, an activator, and a dispersant, and the dispersant is a polycondensate-based dispersant containing polyalkylene glycol monophenyl ether as a partial structure, and the amount of the dispersant is 0.1% by mass to 2.0% by mass relative to the total mass of the geopolymer composition. In addition, the active filler contains 85% by mass or more (relative to the total amount of the active filler) of coal ash and blast furnace slag powder that have not been treated to comply with the standard for fly ash for concrete specified in JIS A 6201:2015.
[0024] In the geopolymer composition according to this embodiment, the hardening speed of the geopolymer composition can be slowed down by the action of the dispersant described above, while the hardening speed retardation action disappears in a few hours, so that it is possible to achieve both high fluidity over a long period of time and strength development in a short period of time. In addition, the addition of the dispersant makes it unnecessary to add a large amount of water to ensure fluidity, and at the same time, by using a specific type and a specific amount of active filler, it is possible to significantly increase the strength of the hardened product of the geopolymer composition. As a result, it is possible to suppress the elution of heavy metals from the hardened product of the geopolymer composition. Furthermore, the coal ash contained as the active filler is mainly coal ash that has not been subjected to special pretreatment to make its quality uniform (specifically, coal ash that has not been treated to comply with the standard for fly ash for concrete specified in JIS A 6201:2015 (hereinafter, also simply referred to as "untreated coal ash")), but the effect of such a geopolymer composition according to this embodiment can be obtained.
[0025] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0026] 1. Geopolymer composition The geopolymer composition in this embodiment contains an active filler, an aggregate, water, an activator, and a polycondensate-based dispersant containing a polyalkylene glycol monophenyl ether as a partial structure. Below, the function of each component and its blending amount, the manufacturing or preparation method of the geopolymer composition, and its physical properties will be described in detail.
[0027] <Active filler> The active filler is a powder containing aluminosilicate, which is active against alkali, as its main component. When an activator (described later) or a small amount of water is added to the active filler, the silicon and aluminum in the active filler are partially dissolved or ionized. After dissolution, the silica, which exists in a state close to a monomer in the alkaline silica solution, takes in metal ions, causing a dehydration condensation reaction, producing a hardened polymer compound (polymer), which becomes the hardened geopolymer composition.
[0028] The geopolymer composition in this embodiment contains, as an active filler, coal ash and ground granulated blast furnace slag that have not been treated to conform to the standard for fly ash for concrete specified in JIS A 6201 in a total amount of 85% by mass or more (relative to the total amount of the active filler). By containing the coal ash and ground granulated blast furnace slag in a total amount of 85% by mass or more, by-products can be efficiently and effectively utilized. On the other hand, if the total amount of these is less than 85% by mass, it cannot be said that the by-products are efficiently and effectively utilized, and there is a possibility that the manufacturing cost will increase. The total amount of untreated coal ash and ground granulated blast furnace slag is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more. Furthermore, it is preferable to contain silica fume as an active filler.
[0029] The function of each of these components and the amount of each component to be added will be described in detail below.
[0030] (coal ash) Coal ash (untreated coal ash) that is included as an active filler and that has not been treated to conform to the standard for fly ash for concrete specified in JIS A 6201:2015 can be obtained, for example, as a by-product generated during coal combustion at a coal-fired power plant or the like, and contains silicon dioxide (SiO2), alumina (Al2O3), and the like as main components. In this specification, coal ash that has not been treated to conform to the standard for fly ash for concrete specified in JIS A 6201:2015 is, in other words, coal ash that has not been subjected to crushing and / or particle size adjustment, preferably particle size adjustment. Or, for example, coal ash that has not been subjected to crushing and / or particle size adjustment, preferably particle size adjustment, is a coal ash that has not been subjected to crushing and / or particle size adjustment, and the like. 2 / g~3600cm 2 The coal ash has a Blaine specific surface area of about 1000 / g and has not been subjected to pulverization and / or particle size adjustment, preferably particle size adjustment. In other words, the coal ash that has not been treated to comply with the standard for fly ash for concrete specified in JIS A 6201:2015 is preferably (untreated) coal ash produced as an industrial by-product from at least one of a thermal power plant and a boiler. In detail, for example, fly ash captured from exhaust gas by a dust collector, bottom ash obtained by pulverizing lumps of ash at the bottom of a boiler, etc. may be mentioned. Two or more types of coal ash may be used in combination.
[0031] According to the geopolymer composition of this embodiment, even if coal ash that has not been treated to comply with the standard for fly ash for concrete specified in JIS A 6201:2015 is used as an active filler, it is possible to obtain the effects of suppressing the elution of heavy metals in the hardened body, which is a molded product, high fluidity of the geopolymer composition itself, and high strength development in a short period of time. In other words, even if the size, composition, heavy metal content range, etc. of the coal ash used are not uniform and there is a certain degree of variation in its quality, the above-mentioned effects can be obtained by using a specific type and a specific amount of dispersant and active filler.
[0032] The amount of untreated coal ash to be mixed with respect to the total mass of the active filler is not particularly limited. For example, the amount of untreated coal ash to be mixed with respect to the total mass of the active filler is preferably 3% by mass to 77% by mass. By making the amount of untreated coal ash to be mixed with respect to the total mass of the active filler 3% by mass or more, coal ash that may be generated as a by-product can be effectively used as a resource, which is environmentally friendly and can reduce production costs. By making the amount of untreated coal ash to be mixed with respect to the total mass of the active filler 77% by mass or less, excessive early strengthening of the geopolymer composition can be prevented. The amount of untreated coal ash to be mixed with respect to the total mass of the active filler is more preferably 40% by mass or more, and even more preferably 60% by mass or more. Moreover, the amount of untreated coal ash to be mixed with respect to the total mass of the active filler is more preferably 73% by mass or less, and even more preferably 70% by mass or less.
[0033] In addition, within a range that does not significantly impair the effect of the present embodiment of efficiently utilizing industrial by-products, a small amount of coal ash that has been treated to conform to the standard for fly ash for concrete specified in JIS A 6201: 2015 (hereinafter, simply referred to as "treated coal ash") may be optionally included as an active filler. Specifically, the amount of treated coal ash mixed with respect to the total mass of the active filler is, for example, less than about 5 mass%.
[0034] (Grained blast furnace slag) The ground granulated blast furnace slag can be obtained, for example, by pulverizing granulated blast furnace slag obtained as a by-product when refining iron in a blast furnace, and contains calcium oxide (CaO), silicon dioxide (SiO2), alumina (Al2O3), etc. as main components. Specifically, the ground granulated blast furnace slag is not particularly limited as long as it is a known product, and a commercially available product may be used. As the commercially available ground granulated blast furnace slag, for example, ground granulated blast furnace slag that meets the standard of JIS A 6206 Ground Blast Furnace Slag 4000 can be used, and in detail, "K-MENT" sold by Kobe Steel Slag Products Co., Ltd., "ESMENT" manufactured by Nippon Steel Blast Furnace Cement Co., Ltd., etc. can be used.
[0035] The amount of ground granulated blast furnace slag powder to the total mass of the active filler is not particularly limited. For example, the amount of ground granulated blast furnace slag powder to the total mass of the active filler is preferably 3% by mass to 77% by mass. By making the amount of ground granulated blast furnace slag powder to the total mass of the active filler 3% by mass or more, by-products can be effectively used as resources, which is environmentally friendly and reduces manufacturing costs. By making the amount of ground granulated blast furnace slag powder to the total mass of the active filler 77% by mass or less, excessive early strengthening of the geopolymer composition can be prevented. The amount of ground granulated blast furnace slag powder to the total mass of the active filler is more preferably 10% by mass or more, and even more preferably 25% by mass or more. Moreover, the amount of ground granulated blast furnace slag powder to the total mass of the active filler is more preferably 50% by mass or less, and even more preferably 35% by mass or less.
[0036] (Silica fume) Silica fume, which is optionally included as an active filler, is a by-product obtained by collecting dust in exhaust gas generated during the manufacture of, for example, ferrosilicon, metallic silicon, electrolytic zirconia, etc., and contains silicon dioxide (SiO2) as a main component. Specifically, silica fume is amorphous spherical fine particles of high-purity silicon dioxide (SiO2).
[0037] Silica fume not only functions as a normal active filler, that is, it acts as the starting point for the dehydration condensation polymerization reaction and leads to an improvement in the strength of the hardened body, but also has the function of increasing the fluidity of the geopolymer composition after mixing because of its spherical shape. Note that commercially available silica fume may be used.
[0038] When silica fume is included as an active filler, the amount of silica fume is not particularly limited, but is preferably 1% by mass to 20% by mass relative to the total mass of the active filler. By making the amount of silica fume to be 1% by mass or more relative to the total mass of the active filler, the above-mentioned action of silica fume can be exhibited. Since silica fume is expensive, by making the amount of silica fume to be 20% by mass or less relative to the total mass of the active filler, the production cost of the geopolymer composition can be reduced. The amount of silica fume to be added relative to the total mass of the active filler is more preferably 3% by mass or more, and even more preferably 5% by mass or more. Moreover, the amount of silica fume to be added relative to the total mass of the active filler is more preferably 15% by mass or less, and even more preferably 13% by mass or less.
[0039] In addition to the above-mentioned coal ash and blast furnace slag powder, and optional silica fume, other components that are active against alkali and can generally be used as active fillers may also be included in the geopolymer composition of this embodiment. For example, red mud, feldspars, micas, zeolites, perlite, clay minerals, kaolin, metakaolin, sewage sludge, etc. may be included as active fillers.
[0040] The amount of active filler can be determined by the ratio with respect to the activator to be blended in the geopolymer composition. Specifically, for example, when an alkaline aqueous solution with a concentration of about 8 mol / L to 10 mol / L is used as the activator, it is preferable to adjust the amount of active filler so that the ratio of the amount of activator to the total amount of active filler (i.e., activator (mass) / active filler (total mass)) is 5% to 30%. The preferred ratio varies somewhat depending on the type and concentration of the activator, but the ratio may be appropriately adjusted according to the type and concentration. For example, when an alkaline aqueous solution with the above-mentioned concentration is used as the activator, by making the activator (mass) / active filler (total mass) 5% or more, the dehydration condensation reaction in the active filler can be sufficiently caused, and a geopolymer hardened body having sufficient strength can be finally obtained. By making the activator (mass) / active filler (total mass) 30% or less, false coagulation due to an excessive amount of activator can be prevented.
[0041] For example, when an alkaline aqueous solution having the above-mentioned concentration is used as an activator, the activator (mass) / active filler (total mass) is more preferably 10% or more, and even more preferably 15% or more, and the activator (mass) / active filler (total mass) is more preferably 25% or less, and even more preferably 20% or less.
[0042] As mentioned above, the total amount of active filler is determined by the ratio with the activator. Meanwhile, the specific total amount of active filler relative to the total mass of the geopolymer composition varies depending on the type of geopolymer hardened body, which is the final product, so it may be adjusted appropriately. Examples of the type of geopolymer hardened body include concrete, mortar, etc.
[0043] <Aggregate> The aggregate is not particularly limited, and known aggregates used in the production of concrete, mortar, artificial stone, etc. may be used. The aggregate may be either a coarse aggregate having a diameter of 5 mm or more in 85% or more, or a fine aggregate having a diameter of 5 mm or less in 85% or more. Alternatively, these may be used in combination. The type of aggregate may be appropriately selected depending on the application of the geopolymer hardened body, which is the final product. Two or more types of aggregate may be used.
[0044] As the fine aggregate, a fine aggregate such as a general silica sand, which is a natural aggregate, may be used, but it is preferable to use a blast furnace slag fine aggregate. The blast furnace slag fine aggregate is specified in JIS A 5011-1:2018. By using the blast furnace slag fine aggregate, the long-term strength of the final product, the hardened geopolymer body, can be increased due to the latent hydraulic property of the blast furnace slag fine aggregate, that is, the property of increasing the strength by generating hydrates due to the silicon dioxide (SiO2), alumina (Al2O3), etc. contained in the blast furnace slag fine aggregate. The blast furnace slag fine aggregate may be a commercially available product. Examples of commercially available blast furnace slag fine aggregate include "Shinko Sand" sold by Kobe Steel Slag Products Co., Ltd. and blast furnace slag fine aggregate manufactured by JFE Mineral Co., Ltd.
[0045] Regardless of whether fine aggregate or coarse aggregate is used as the aggregate, it is particularly preferable to use aggregate made from blast furnace slag (i.e., blast furnace slag fine aggregate and blast furnace slag coarse aggregate) from the viewpoints that by-products can be effectively utilized as resources, they are highly environmentally compatible, and production costs can be reduced.
[0046] When fine aggregate is included as an aggregate, the amount of fine aggregate relative to the total mass of the geopolymer composition is not particularly limited, and may be adjusted according to the intended use of the geopolymer hardened body, which is the final product. For example, the amount of fine aggregate relative to the total mass of the geopolymer composition is preferably 30% by mass to 70% by mass. By making the amount of fine aggregate relative to the total mass of the geopolymer composition 30% by mass or more, sufficient strength can be imparted to the final product, the geopolymer hardened body. By making the amount of fine aggregate relative to the total mass of the geopolymer composition 70% by mass or less, the proportion of active filler in the composition is reduced, thereby avoiding a decrease in the strength of the hardened geopolymer composition.
[0047] Furthermore, when fine aggregate is included as the aggregate, the amount of the fine aggregate mixed relative to the total mass of the geopolymer composition is more preferably 40% by mass to 60% by mass.
[0048] <Water (also called "added water")> The type of water is not particularly limited, and may be tap water. Furthermore, the pH and temperature of the water are also arbitrary, and may be appropriately adjusted to general values according to the type and amount of each component contained in the geopolymer composition. In addition, the water may contain waste alkaline water, etc., as long as it does not affect the effects of this embodiment, such as the fluidity of the geopolymer composition according to this embodiment.
[0049] Water contributes to the fluidity of the geopolymer composition, but the geopolymer composition in this embodiment contains a dispersant described later, which can significantly increase the fluidity of the composition. Therefore, the amount of water to be blended may be very small. Specifically, the amount of water to be blended relative to the total mass of the geopolymer composition is preferably 1.5% by mass to 6% by mass. By making the amount of water to be blended relative to the total mass of the geopolymer composition 1.5% by mass or more, it is possible to prevent the fluidity of the geopolymer composition after blending from decreasing significantly. By suppressing the amount of water to be blended relative to the total mass of the geopolymer composition to 6% by mass or less, it is possible to more reliably develop the strength of the hardened body in a short period of time without performing complex treatments such as steam curing, and it is possible to obtain a hardened body with extremely high strength.
[0050] Moreover, the amount of water to be blended with respect to the total mass of the geopolymer composition is more preferably 2% by mass to 5% by mass.
[0051] <Activator> The activator is a component that is the starting point for polymerization by dehydration condensation reaction of the active filler, and is an alkaline aqueous solution that comes into contact with the aluminosilicate in the active filler and dissolves silicon and aluminum. The activator is not particularly limited as long as it is a commonly used one, and for example, sodium hydroxide, sodium silicate (water glass), potassium silicate, etc. can be used.
[0052] The concentration of the alkaline aqueous solution as the activator is not particularly limited, and is preferably, for example, 6 mol / L to 12 mol / L. The preferred concentration range varies somewhat depending on the type and content of the activator, but may be adjusted appropriately. By setting the activator concentration to 6 mol / L or more, the dehydration condensation reaction in the active filler can be sufficiently caused. By setting the activator concentration to 12 mol / L or less, the generation of excessive heat of fusion due to high concentration can be avoided.
[0053] The concentration of the aqueous alkaline solution as the activator must be adjusted appropriately depending on the type and content of the activator, but is more preferably 7 mol / L or more, and even more preferably 8 mol / L or more. The concentration of the aqueous alkaline solution as the activator must be adjusted appropriately depending on the type and content of the activator, but is more preferably 11 mol / L or less, and even more preferably 10 mol / L or less.
[0054] The amount of the activator can be determined in the same manner as described above based on the ratio to the total amount of the active filler to be mixed in the geopolymer composition.
[0055] <Dispersant> The geopolymer composition in this embodiment contains a polycondensate-based dispersant (hereinafter also simply referred to as "dispersant") containing polyalkylene glycol monophenyl ether as a partial structure.
[0056] By including the dispersant in the geopolymer composition, the particles in the geopolymer composition can be dispersed, and the hardening reaction of the geopolymer composition can be slowed down. In addition, the hardening reaction retardation effect of the dispersant disappears in a few hours. Therefore, according to the geopolymer composition of this embodiment, it is not necessary to add a large amount of water to ensure the fluidity of the geopolymer composition for a long time, for the purpose of improving the handling at the manufacturing site, etc. As a result, the problems of the long time required for the hardened body to develop its strength and the insufficient strength of the hardened body after curing, which were caused by adding a large amount of water, can be solved.
[0057] In this specification, the polycondensate-based dispersant containing polyalkylene glycol monophenyl ether as a partial structure is not particularly limited as long as it is a polymer having the above-mentioned function and a specified structure. For example, such a dispersant includes a polymer containing at least one polycondensate containing the following structural unit A, structural unit B, structural unit C, and structural unit D.
[0058] Structural unit A: polyethylene glycol monophenyl ether represented by the following formula (I)
[0059] [ka] [In the formula (I), m is an integer of 3 to 280.]
[0060] Structural unit B: A cyclic compound having at least one hydroxyl group and a derivative thereof, for example, a structural unit containing at least one aromatic compound selected from the group consisting of benzene-1,2-diol, benzene-1,2,3-triol, 2-hydroxybenzoic acid, 2,3-dihydroxybenzoic acid, 3,4-dihydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid, 3-hydroxyphthalic acid, 2,3-dihydroxybenzenesulfonic acid, 3,4-dihydroxybenzenesulfonic acid, 1,2-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 1,2-dihydroxynaphthalene-5-sulfonic acid, 1,2-dihydroxynaphthalene-6-sulfonic acid, 2,3-dihydroxynaphthalene-5-sulfonic acid, 2,3-dihydroxynaphthalene-6-sulfonic acid, and mixtures thereof.
[0061] Structural unit C: phenol, polyethylene glycol monophenyl ether having 1 or 2 ethylene oxide repeating units, or phenoxyethyl derivatives containing phosphate or phosphonate, such as a structural unit containing at least one other aromatic compound selected from the group consisting of phenol, 2-phenoxyethanol, 2-phenoxyethyl phosphate, 2-phenoxyethyl phosphonate, 2-phenoxyacetic acid, 2-(2-phenoxyethoxy)ethanol, 2-(2-phenoxyethoxy)ethyl phosphate, 2-(2-phenoxyethoxy)ethyl phosphonate, 2-[4-(2-hydroxyethoxy)phenoxy]ethyl phosphate, 2-[4-(2-hydroxyethoxy)phenoxy]ethyl phosphonate, 2-[4-(2-phosphonatooxyethoxy)phenoxy]ethyl phosphate, 2-[4-(2-phosphonatooxyethoxy)phenoxy]ethyl phosphonate, methoxyphenol, and mixtures thereof.
[0062] Structural unit D: Aldehydes, for example, a structural unit containing at least one aldehyde selected from the group consisting of formaldehyde, paraformaldehyde, glyoxylic acid, benzaldehyde, benzaldehyde sulfonic acid, benzaldehyde disulfonic acid, vanillin, isovanillin, and mixtures thereof.
[0063] The amount of dispersant to be blended relative to the total mass of the geopolymer composition is 0.1% by mass to 2.0% by mass. By making the amount of dispersant to be blended relative to the total mass of the geopolymer composition 0.1% by mass or more, the above-mentioned action of the dispersant can be exerted. By making the amount of dispersant to be blended relative to the total mass of the geopolymer composition 2.0% by mass or less, the occurrence of separation and bleeding of the geopolymer composition due to the addition of excessive dispersant can be suppressed.
[0064] The amount of the dispersant based on the total mass of the geopolymer composition is preferably 0.5% by mass or more.
[0065] <Other ingredients> The geopolymer composition in this embodiment may contain any material that is generally added as a raw material for mortar, concrete, etc., as long as it does not impair the effect of this embodiment. For example, unlike the active filler described in detail above, it may contain an inactive filler, which is a powder that has no activity against alkali, various additives, etc. Examples of inactive fillers that are powders that have no activity against alkali include cement and calcium carbonate. The various additives are not particularly limited, but include conventionally known components such as fluidizers, shrinkage reducing agents, rust inhibitors, waterproofing agents, defoamers, dust reducing agents, and pigments.
[0066] <Method of manufacturing or preparing geopolymer composition> The geopolymer composition in this embodiment can be manufactured or prepared by a conventionally known method. For example, the manufacturing or preparation method of the geopolymer composition includes a powder mixing step in which an active filler containing untreated coal ash and blast furnace slag powder (and optional silica fume), which are the main powder raw materials, and an aggregate are mixed in a predetermined blending amount, and a kneading step in which water, an activator, and a dispersant are added in a predetermined blending amount and mixed and kneaded after the powder mixing step. The mixing method and kneading method are not particularly limited, and a known method using a mixer or the like may be used.
[0067] In addition, in the above-mentioned method for producing or preparing a geopolymer composition, the active filler containing coal ash, blast furnace slag powder and silica fume, which are the main powder raw materials, and the aggregate are mixed in a predetermined amount to obtain a powder mixture, which may be used as a premixed geopolymer composition. The premixed geopolymer composition is prepared in advance, and water, an activator and a dispersant are further added to the premixed geopolymer composition in a predetermined amount before construction, work, etc., and mixed and kneaded. This allows any desired amount of geopolymer composition to be easily produced or prepared on site.
[0068] <Physical properties of geopolymer composition> In the present embodiment, the geopolymer composition preferably has a uniaxial compressive strength of 10 MPa or more at 7 days of age, as measured in accordance with JIS A 1108:2018 for the hardened product of the geopolymer composition. In this specification, the term "hardened product of the geopolymer composition" used in relation to the physical property of the uniaxial compressive strength of the geopolymer composition refers to a hardened molded body obtained by loading the geopolymer composition into a cylindrical mold having a diameter of 5 cm and a height of 10 cm, sealing and curing the composition for a predetermined period of time, and then demolding the molded product, as described in the following examples.
[0069] By having the uniaxial compressive strength of the hardened geopolymer composition be 10 MPa or more at 7 days of age, it is possible to more reliably suppress the elution of heavy metals contained in the raw material coal ash, etc. In this specification, heavy metals refer to heavy metals that are subject to emission standards for soil and rivers, for example, and specifically refer to As, B, Se, Pb, Cd, F, Hg, Cr, etc., which are described in the Guidelines for Effective Use of Coal Ash Mixtures issued by the Coal Frontier Foundation.
[0070] The unconfined compressive strength of the hardened geopolymer composition at 7 days of age, measured in accordance with JIS A 1108:2018, is more preferably 27 MPa or more, even more preferably 30 MPa or more, and particularly preferably 32.5 MPa or more. The upper limit of the unconfined compressive strength of the hardened geopolymer composition is not particularly limited, but considering the strength of the hardened geopolymer composition that can be actually produced, it is considered to be about 65 MPa or less at the age of 28. In this specification, the unconfined compressive strength of the hardened geopolymer composition is, more specifically, the strength measured by the method described in the following examples.
[0071] Alternatively, in the geopolymer composition of this embodiment, the bending crack resistance of the hardened product of the geopolymer composition measured in accordance with JIS A 5371:2016 is preferably 3.5 kN·m or more at an age of 5 days, more preferably 4.0 kN·m or more. By having the bending crack resistance of the hardened product of the geopolymer composition be 3.5 kN·m or more at an age of 5 days, the elution of heavy metals contained in the raw material coal ash etc. can be more reliably suppressed. In this specification, the bending crack resistance of the hardened product of the geopolymer composition is, more specifically, the resistance measured by the method described in the following examples.
[0072] According to the geopolymer composition of this embodiment, a hardened body capable of suppressing the elution of heavy metals can be produced. Furthermore, the geopolymer composition of this embodiment can ensure high fluidity for a long time and high strength in a short time by a simple method. In addition, in this embodiment, coal ash that has not been treated to comply with the standard for fly ash for concrete specified in JIS A 6201:2015, which has a certain degree of quality variation, is used as an active filler, and the effect of this embodiment can be obtained.
[0073] 2. Hardened geopolymer The geopolymer hardened body in this embodiment is a hardened product of the geopolymer composition in the above-mentioned embodiment, specifically a hardened product having any shape formed by any molding method, construction method, etc. In detail, the geopolymer composition manufactured or prepared as described above is molded or constructed using a known method such as molding using a formwork, troweling in plastering work, spraying, or pasting, and then the geopolymer hardened body can be produced by normal curing, such as in air or sealing, without performing steam curing or autoclave curing.
[0074] In addition, when the geopolymer composition in the above-mentioned embodiment is used to make a geopolymer hardened body in this embodiment using a formwork, it is preferable to apply a release agent or the like to the formwork in advance. The release agent is not particularly limited as long as it imparts release properties to the hardened geopolymer composition.
[0075] The geopolymer hardened body in this embodiment is not particularly limited, but examples thereof include road or bank blocks, blocks for storm water channels or irrigation channels, tiles, bricks, sewer pipes, piles, poles, precast products such as sleepers, cast-in-place concrete, sprayed concrete, concrete repair, dam concrete, and other cast-in-place products.
[0076] The geopolymer hardened body of this embodiment can suppress the elution of heavy metals, and can therefore be suitably used in various products in which the impact on the environment or human body is taken into consideration. For example, it can be suitably used in floor slabs, racks, various drainage pipes, gutter blocks, sidewalk boundary blocks, revetment blocks, retaining walls, boxes, poles or piles buried in the ground or underwater, etc., which are applied in contact with soil, rivers, etc. EXAMPLES
[0077] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0078] In this example, various geopolymer compositions were actually prepared by changing the amount of raw materials used, and the fluidity of the geopolymer compositions was evaluated, and a uniaxial compressive strength test of the hardened geopolymer composition, a bending strength test of the hardened geopolymer composition, and a heavy metal elution test of the hardened geopolymer composition were performed.
[0079] [Preparation of Geopolymer Composition] Each of the raw materials shown in Table 1 below was mixed in each mass% (relative to the total mass of the composition) to prepare geopolymer compositions in Examples 1 to 4 and Comparative Example 1. Specifically, first, coal ash (untreated coal ash), ground granulated blast furnace slag, and silica fume were mixed in the following amounts, and fine blast furnace slag aggregate (as well as slowly cooled blast furnace slag and / or silica sand) was added as aggregate to the mixed powder and mixed. Finally, an aqueous solution of the activator, a dispersant, and added water in each amount were added and mixed. Note that the geopolymer compositions were prepared by kneading the mixture using a Hobart mixer for Examples 1, 2, 4, and Comparative Example 1, and a two-shaft paddle mixer for Example 3.
[0080] [Table 1]
[0081] As coal ash, coal ash collected at thermal power plants, specifically, fly ash captured by an electric dust collector, and bottom ash that adheres and grows inside a boiler and is crushed by a crusher were used as they are. In other words, coal ash, which is an industrial by-product, was used as untreated coal ash without strict pretreatment to make the quality uniform (in other words, treatment to make it conform to the standard for fly ash for concrete specified in JIS A 6201:2015). In addition, in Examples 1 and 2, only fly ash was used. In Examples 3, 4, and Comparative Example 1, a mixture of fly ash and bottom ash was used. As the granulated blast furnace slag, "K-MENT" manufactured by Kobe Steel Slag Products Co., Ltd. was used. The physical properties of K-MENT are, for example, a specific surface area of 4700 cm 2 / g. As the silica fume, "Mastercrete SF 5000" manufactured by Pozzolith Solutions was used. As the aggregate, mainly blast furnace slag fine aggregate, specifically "Shinko Sand" manufactured by Kobe Steel Slag Products Co., Ltd., was used. The properties of Shinko Sand are, for example, a maximum particle size of 2.5 mm, and a sieve passing mass fraction of a sieve with a nominal size of 0.6 mm of 55%. Thus, in Examples 1 to 4 and Comparative Example 1, the active filler contained untreated coal ash, ground granulated blast furnace slag, and silica fume in a total amount of 100 mass%.
[0082] In the geopolymer composition of Example 1, as shown in Table 1 above, not only fine blast furnace slag aggregate but also silica sand with a particle size of about the same size was included in the mixture amount of 11.2 mass%. In addition, in the geopolymer composition of Example 3, blast furnace slag with a particle size adjusted to 5 mm to 32 mm, which is a larger particle size aggregate, was also included as an aggregate.
[0083] The activator used was "Mastercrete AC 5025" manufactured by Pozzolith Solutions, Inc. The dispersant used was the compound described in Example 5 of Japanese Patent No. 6290176.
[0084] [Evaluation of fluidity of geopolymer composition] The fluidity of each geopolymer composition prepared as described above was evaluated by measuring it in accordance with the flow test specified in JIS R 5201:2015 (physical test method for cement). However, the flow test was performed without tamping. Note that the geopolymer composition of Example 3 contained coarse particles in the raw aggregate, so it was measured in accordance with JIS A 1101:2005 (slump test method for concrete). The measurement results are shown in Table 2 below. Note that "-" in Table 2 indicates that it has not been measured.
[0085] [Table 2]
[0086] As shown in Table 2 above, the geopolymer compositions of Examples 1, 2, and 4 had a flow value of 200 mm or more after 120 minutes even with a small amount of added water because a dispersant was added, and maintained high fluidity. The geopolymer composition of Example 3, which had a small amount of added water and a dispersant added like the other examples, was only measured after 10 minutes, but from the state of the composition at that time, it was observed that it was expected to have a sufficiently high fluidity even after 120 minutes. On the other hand, the geopolymer composition of Comparative Example 1, which had a large amount of added water and no added dispersant, had a low fluidity of 100 mm in all measurements.
[0087] [Uniaxial compressive strength test of hardened geopolymer composition] The uniaxial compressive strength of the hardened product of each geopolymer composition prepared as described above was measured. The uniaxial compressive strength was measured by placing each geopolymer composition in a cylindrical mold with a diameter of 5 cm and a height of 10 cm, sealing and curing it for a specified period of time, and then removing the molded product from the mold using the method specified in JIS A 1108:2018.
[0088] In the unconfined compressive strength test of the geopolymer composition of Example 4, the geopolymer composition in the substitute mix example KT1, which has a very similar blending amount of each raw material shown in Table 3 below, was used instead. Even when testing using a molded product of the geopolymer composition of the substitute mix example KT1, it is expected that there will be almost no difference in unconfined compressive strength compared to the mix of the geopolymer composition of Example 4. The measurement results of the unconfined compressive strength test at each age date (strength measurement date) are shown in Table 4 below. In Table 4, "-" indicates that no measurement was performed.
[0089] [Table 3]
[0090] [Table 4]
[0091] As shown in Table 4 above, the geopolymer compositions of Examples 1, 2, and 4, which had a dispersant added and a small amount of added water, had a high unconfined compressive strength of 27 MPa or more after only 7 days of sealed curing. In other words, the unconfined compressive strength of the hardened product was 24 N / mm2, which is the standard value for compressive strength of pavement and boundary blocks specified in Appendix B of JIS A 5371:2016. 2 On the other hand, the geopolymer composition of Comparative Example 1, which had no dispersant added and had a large amount of added water, was sealed and cured for two days, and the uniaxial compressive strength was measured. However, the strength was extremely low, and the composition collapsed during the measurement.
[0092] [Bending crack resistance test of hardened geopolymer composition] The bending crack resistance of the hardened geopolymer composition of Example 3 prepared as described above was measured. Specifically, the bending crack resistance of the hardened geopolymer composition was measured in accordance with the bending crack resistance test of concrete specified in JIS A 5371:2016. As a result, the bending crack resistance of the hardened geopolymer composition of Example 3 after 5 days of sealed curing was 4.67 kN·m, which was significantly larger than that of a typical hardened geopolymer. In other words, it greatly exceeded the standard value of the nominal A bending crack resistance of the block specified in the recommended specification B-2 for boundary blocks in Appendix B of JIS A 5371:2016. From these results, it is estimated that the uniaxial compressive strength of the hardened material of the geopolymer composition of Example 3, which has a dispersant added and a small amount of added water, will be similar to the uniaxial compressive strength of the hardened materials of the geopolymer compositions of Examples 1, 2, and 4 described above, and will exhibit high strength after several days of sealed curing (e.g., after 7 days of sealed curing).
[0093] [Heavy metal elution test of hardened geopolymer composition] For each geopolymer composition, the amount of heavy metal elution in the hardened product was measured. Specifically, as in the uniaxial compressive strength test, a heavy metal elution test was carried out on a molded product of each geopolymer composition with a diameter of 5 cm and a height of 10 cm under the test conditions specified in JIS K 0058-1:2005, 5., to measure the amount of heavy metal elution. For the geopolymer composition of Example 3, the mortar portion was sieved and a heavy metal elution test was carried out.
[0094] In the heavy metal elution test, the geopolymer composition in the substitute blend example KTT1-2, which has a very similar blend amount of each raw material shown in Table 5 below, was used instead of the geopolymer compositions in Examples 1 and 2 described above. Even when evaluating using the hardened geopolymer composition of the substitute blend example, it is expected that there is almost no difference in factors that affect heavy metal elution compared to the blends in Examples 1 and 2. Furthermore, the results of the heavy metal elution test are shown in Table 6 below. In addition, Table 6 below also shows the elution standards (general use) described in the Guidelines for Effective Use of Coal Ash Mixed Materials issued by the Coal Frontier Foundation. In Table 6, "-" indicates that it has not been measured.
[0095] [Table 5]
[0096] [Table 6]
[0097] As can be seen from Table 6 above, the hardened geopolymer compositions of Examples 1 to 4, which had a high uniaxial compressive strength or high bending crack resistance due to the addition of a dispersant and a small amount of added water, were able to suppress the amount of heavy metal elution. On the other hand, the hardened geopolymer composition of Comparative Example 1, which had a large amount of added water and no dispersant added, and whose uniaxial compressive strength was too low to measure, met the elution standard (for general use), but had an increased amount of heavy metal elution compared to Examples 1 to 4.
[0098] (Consideration) In summary, the geopolymer compositions of Examples 1 to 4 were added with a specific type of dispersant in a specific blend amount, which delayed the hardening reaction and ensured high fluidity for a longer period of time even with a reduced amount of added water (see Table 2 above). Furthermore, in the geopolymer compositions of Examples 1 to 4, the action of the dispersant disappeared in a few hours, so that strength could be developed in a short period of time, and because the amount of added water was small and a specific type of active filler in a specific range of blend amount was used, all of them exhibited high strength (uniaxial compressive strength or bending crack resistance) (see Table 4 above). In addition, it is assumed that the hardened products of the geopolymer compositions of Examples 1 to 4 exhibited high strength (uniaxial compressive strength or bending crack resistance), and therefore the amount of metal elution from the hardened body could be suppressed (see Table 6 above). In addition, in these examples, untreated coal ash, which is an industrial by-product, is used as the active filler without strict pretreatment. For this reason, even if untreated coal ash, an industrial by-product with varying quality in terms of particle size, etc., is used as a raw material, it is possible to suppress the amount of metal leaching from the hardened geopolymer body, which is beneficial from the standpoint of reducing the environmental impact and reducing manufacturing costs.
[0099] On the other hand, the geopolymer composition of Comparative Example 1 was mixed with a large amount of added water in order to ensure a certain degree of fluidity without containing a dispersant. Therefore, the hardened material of the geopolymer composition of Comparative Example 1 was unable to exhibit high strength (uniaxial compressive strength), which ultimately led to the elution of more heavy metals.
Claims
1. A method for producing a geopolymer hardened body, comprising: a powder mixing step of mixing an active filler with an aggregate; a kneading step of adding water, an activator, and a dispersant to the mixture after the powder mixing step, and mixing and kneading the mixture; and curing the prepared geopolymer composition. In the above curing, neither steam curing nor autoclave curing is performed, The dispersant is a polycondensate-based dispersant containing polyalkylene glycol monophenyl ether as a partial structure, and the amount of the polycondensate is 0.1% by mass to 2.0% by mass based on the total mass of the geopolymer composition. The amount of water is 6% by mass or less based on the total mass of the geopolymer composition, The active filler contains 85% by mass or more of coal ash and blast furnace slag powder that have not been treated to conform to the standard for fly ash for concrete specified in JIS A 6201. A method for producing a geopolymer hardened body.
2. The method for producing a hardened geopolymer body according to claim 1, wherein the active filler further comprises silica fume.
3. The method for producing a geopolymer hardened body according to claim 1 or 2, wherein the aggregate includes at least one of a blast furnace slag fine aggregate, a blast furnace slag coarse aggregate, and a natural aggregate.
4. The method for producing a geopolymer hardened body according to any one of claims 1 to 3, wherein the uniaxial compressive strength of the geopolymer hardened body measured in accordance with JIS A 1108 is 10 MPa or more at a material age of 7 days.
5. The method for producing a geopolymer hardened body according to any one of claims 1 to 3, wherein the bending crack resistance of the geopolymer hardened body measured in accordance with JIS A 5371 is 3.5 kN · m or more at a material age of 5 days.
6. The method for producing a geopolymer hardened body according to any one of claims 1 to 5, wherein the amount of water is 1.5% by mass or more with respect to the total mass of the geopolymer composition.
7. The total amount of the water, the activator and the dispersant is 11.1% by mass or less based on the total mass of the geopolymer composition. The method for producing a hardened geopolymer according to any one of claims 1 to 6.
Citation Information
Patent Citations
Character correcting device
JP1987084388A
Aromatic compound polycondensates, their manufacturing methods, and their uses
JP2015518506A
Method for producing geopolymer hardened body
JP2017100905A
Method for solidification of low calcium fluidized bed coal ash and solidified substance
JP2017113730A
Geopolymer composition and geopolymer-cured body
JP2019014617A